Mass spectrometry-based lipidomics analysis using methyl tert-butyl ether extraction in human hepatocellular carcinoma tissues1. Issue 19 (7th October 2015) - Jiang, Shuxia; Li, Yongle; Lin, Shuhai; Yang, Hongbo; Guan, Xin-yuan; Zhou, Haiyun; Luan, Tiangang; Cai, Zongwei
<x xml:space="preserve">Abstract</x> Lipidomics was applied to analyse irregular metabolites in HCC tissues through a LC-MS method which revealed great changes between HCT and ANT.